Bamboo fiber has engineering properties and performance suitable as reinforcement for asphalt mixture. (5th July 2021) - Liu, Kefei; Li, Teng; Wu, Chaofan; Jiang, Kang; Shi, Xianming
Highlights: Bamboo fiber effectively decreases the temperature sensitivity of asphalt mastic. Bamboo fiber-reinforced asphalt mixture has excellent road performance. Bamboo fiber delays and controls the occurrence and development of large cracks in the mixture. Bamboo fiber is a viable alternative to lignin fiber, contributing to sustainable pavements. Abstract: Bamboo is a plant species that features fast-growing characteristics, and bamboo fiber is a kind of environmentally attractive fiber, which is affordable, recyclable, degradable and renewable. This exploratory study entails laboratory tests conducted to evaluate the potential impact of bamboo fiber on the properties of asphalt mastic and mixture, in comparison to that of lignin fiber. To analyze the road performance and reinforcement mechanism of bamboo fiber asphalt mixture, three kinds of fiber asphalt mastics and mixtures, non-fiber, lignin fiber and bamboo fiber, were prepared. The thermal properties of asphalt mastic and the mechanical properties, high-temperature property, low-temperature property, moisture susceptibility and anti-aging property of asphalt mixtures were tested. Finally, the mechanism of interactions between fiber and mixture was revealed using a scanning electron microscope. Both types of plant fiber can improve the degree of crosslinking between asphalt molecules, thus slightly improving the thermal stability of asphalt mastic at high temperature and effectively decrease its temperature sensitivity. The mechanical properties of lignin fiber asphalt mixture outperformed those of bamboo fiber, while the bamboo fiber asphalt mixture exhibited excellent road performance (especially high-temperature stability, low-temperature crack resistance and moisture stability), notably better than that of lignin fiber. Bamboo fiber can form a close connection with mixture and increase the proportion of structural asphalt in the mixture through adsorption. Both adsorption and mechanical anchoring can reduce the temperature sensitivity and moisture sensitivity of the fiber-reinforced asphalt mixture. The distributed fibers can form a three-dimensional network structure in the asphalt mixture, delaying and controlling the occurrence and development of large cracks in the mixture. Bamboo fiber is a viable substitute for lignin fiber, and its beneficial effects on asphalt mixture might be enhanced in the future by further engineering its surface microstructure and chemistry and improving its dispersion.